АЛИШЕР НАВОИЙ АСАРЛАРИДАГИ «МЕВА» СЎЗИНИНГ ЛЕКСИК-СЕМАНТИК ХУСУСИЯТЛАРИ - Усманова, М.С. (SCIENCE and SOCIETY, 2022)
This article presents the lexical and semantic features of the word "fruit" in the works of Alisher Navoi, the analysis of words used instead of the word "fruit" in modern Uzbek, the conclusions based on research on the use of the word "garden".